A Secure and Synthesis Tele-Ophthalmology System - WEI, Zhuo (Institutional Knowledge at Singapore Management University, 2008)
This paper describes a secure and synthesis ophthalmology telemedicine system, referred to as TeleOph. Under a Secure Socket Layer (SSL) channel, patient prerecorded data can be safely transferred via the Internet. With encrypted videoconference and white-board, the system not only supports hospital-to-clinic consultation, but also supplies hospital-tohospital joint discussion. Based on Directshow technology (Microsoft Corporation, Redmond, WA), video cameras connected to the computer by firewire can be captured and controlled to sample video data. By using TWAIN technology, the system automatically identifies networked still cameras (on fundus and slitlamp devices) and retrieves images. All the images are stored in a selected format (such as JPEG, DICOM, BMP). Besides offline-transferring prerecorded data, the system also supplies online sampling of patient data (real-time capturing from remote places). The system was deployed at Tan Tock Seng Hospital, Singapore and Ang Mo Kio, Singapore, where 100 patients were enrolled in the system for examination. TeleOph can be successfully used for patient consultation, and hospital joint discussion. Meanwhile, TeleOph can supply both offline and online sampling of patient data.